Evaluation of Traditional Indian Antidiabetic Medicinal Plants for Human Pancreatic Amylase Inhibitory Effect In Vitro. (23rd September 2010) - Ponnusamy, Sudha; Ravindran, Remya; Zinjarde, Smita; Bhargava, Shobha; Ravi Kumar, Ameeta
Abstract : Pancreatic α -amylase inhibitors offer an effective strategy to lower the levels of post prandial hyperglycemia via control of starch breakdown. Eleven Ayurvedic Indian medicinal plants with known hypoglycemic properties were subjected to sequential solvent extraction and tested for α -amylase inhibition, in order to assess and evaluate their inhibitory potential on pancreatic α -amylase. Analysis of 91 extracts, showed that 10 exhibited strong Human Pancreatic Amylase (HPA) inhibitory potential. Of these, 6 extracts showed concentration dependent inhibition with IC 50 values, namely, cold and hot water extracts from Ficus bengalensis bark (4.4 and 125 μ g m L - 1 ), Syzygium cumini seeds (42.1 and 4.1 μ g m L - 1 ), isopropanol extracts of Cinnamomum verum leaves (1.0 μ g m L - 1 ) and Curcuma longa rhizome (0.16 μ g m L - 1 ). The other 4 extracts exhibited concentration independent inhibition, namely, methanol extract of Bixa orellana leaves (49 μ g m L - 1 ), isopropanol extract from Murraya koenigii leaves (127 μ g m L - 1 ), acetone extracts from C. longa rhizome (7.4 μ g m L - 1 ) and Tribulus terrestris seeds (511 μ g m L - 1 ). Thus, the probable mechanism of action of the above fractions is due to their inhibitory action on HPA, thereby reducing the rate of starch hydrolysis leading to lowered glucose levels. Phytochemical analysis revealed the presence of alkaloids, proteins, tannins, cardiac glycosides, flavonoids, saponins and steroids as probable inhibitory compounds.